Battery Energy Storage System Strategy for Island System Based on Reliability Assessment - Nestor Gonzalez Cabrera (Energies)
To meet the targets of the 2030 agenda of the United Nations (UN) to reduce CO2 emissions, various small-scale renewable generation sources have been integrated into electricity systems to maintain decarbonisation and reduce the use of thermal generation, aiming to achieve the sustainable development of electricity generation. In this context, this paper introduces a battery-based strategy with the integration of small-scale renewable generation sources. This is evaluated through an analysis of the reliability of transmission lines, considering contingencies of the orders of N-1 and N-2 to identify cases where there are isolated nodes and to visualise the cases with maximum load shedding in the system, indirectly affecting nodes close to the isolated nodes. The proposed strategy is analysed in a six-node RBTS and adapted to the IEEE 118-node system, obtaining energy-efficient results and a reduction in reliability indices.